A Serologic Survey on Canine Leishmaniasis in Kocaeli, Sakarya, Mersin and Elazig Provinces of Turkey - Utuk, A. E.; Gokmen, Guven T.; Bolacali, M.; Balkaya, I; Simsek, S. (Israel Veterinary Medical Assoc, 2018)
The aims of this pilot study were to determine the seroprevalence of canine leishmaniasis in Kocaeli, Sakarya, Mersin and Elazig provinces and make a general evaluation of the serologic prevelence of Canine Leishmaniasis (CanL) in Turkey. For this purpose, 111 sera were collected from dogs of different breeds, ages and sexes. Anti-Leishmania IgG antibodies were detected with a commercially available IFAT kit. The relationship between location, breed, age, sex and the seropositivity were evaluated with Chi Square (X-2) test. At the end of the study, the overall seroprevalence was determined as 7.20% (8/111). Seroprevalance rates were 5%, 10.52% and 18.75% in Sakarya, Kocaeli and Mersin provinces, respectively; however, no antibodies were detected in dogs from Elazig. There was no statistical difference in breed, sex and age groups (P>0.05). The prevalence of infection in the province of Mersin was significantly higher than in Elazig (p<0.05). The mean seroprevalence of CanL was calculated as 7.29% for Turkey, which is similar to our results (7.20%). In this study, we gave information about the serostatus of CanL in four different provinces of Turkey. We consider that further studies are required for a clearer understanding of the parasite epidemiology and effective control measures.
Keywords: Leishmania; IFAT; Dog; Seroprevalance; Turkey